Therapeutic Potential of Intravenous Immunoglobulin in Acute Brain Injury - Thom, Vivien; Arumugam, Thiruma V.; Magnus, Tim; Gelderblom, Mathias (Frontiers in Immunology, 2017)
Acute ischaemic and traumatic injury of the central nervous system (CNS) is known to induce a cascade of inflammatory events that lead to secondary tissue damage. In particular, the sterile inflammatory response in stroke has been intensively investigated in the last decade, and numerous experimental studies demonstrated the neuroprotective potential of a targeted modulation of the immune system. Among the investigated immunomodulatory agents, intravenous immunoglobulin (IVIg) stand out due to their beneficial therapeutic potential in experimental stroke as well as several other experimental models of acute brain injuries, which are characterized by a rapidly evolving sterile inflammatory response, e.g. trauma, subarachnoid haemorrhage. IVIg are therapeutic preparations of polyclonal IgG, extracted from the plasma of thousands of donors. In clinical practice IVIg are the treatment of choice for diverse autoimmune diseases and various mechanisms of action have been proposed. Only recently, several experimental studies implicated a therapeutic potential of IVIg even in models of acute CNS injury, and suggested that the immune system as well as neuronal cells can directly be targeted by IVIg. This review gives further insight into the role of secondary inflammation in acute brain injury with an emphasis on stroke, and investigates the therapeutic potential of IVIG.